COMMON ORAL HEALTH ISSUES AMONG ELDERLY PATIENTS ATTENDING A TERTIARY CARE HOSPITAL IN WESTERN TAMIL NADU, INDIA: A CROSS-SECTIONAL STUDY - SRINIVASAN, SRIRAM BALAJI; GM, SHARAVANAN; ELANGO, VIDHYA; SHANMUGAM, JEEVITHAN (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: Oral health is a pivotal and underestimated domain, especially among the various facets of our health. From the wear and tear accumulated over decades of use to the interplay of chronic health conditions and medications, the elderly population faces a distinct set of oral health concerns that demand careful attention and proactive management. Understanding the complex relationship between oral health and aging is essential, not only for promoting healthy smiles but also for safeguarding the overall well-being and quality of life of older adults. To address this concern, we conducted a study to identify the common oral health problems for the elderly attending a tertiary care hospital in Western Tamil Nadu, India. Methods: This cross-sectional study was done among 384 elderly adults and senior citizens who attended the Dentistry Outpatient Department (OPD) of a tertiary care center in Coimbatore, Western Tamil Nadu, India. A structured questionnaire was used to collect disease information and demographic data. Results: When assessed for common oral health conditions, 61.4% had periodontal diseases, 65% had dental caries, 13.8% had oral mucosal lesions, 55.5% had sensitive teeth, 13.3% had dry mouth, and 48.6% had edentulism. Conclusion: The data presented in the present study explains the significance of various dental conditions among the study population. It reinforces the imperative of providing comprehensive oral healthcare and prioritizing preventive measures. Taking proactive steps to address these dental concerns, including scheduling regular dental check-ups, instilling proper oral hygiene practices, and intervening early when necessary is paramount in fostering ideal oral health and overall well-being among older adults.